The image of the modern museum: from the world of the Muse - to the Disneyland (Journal of Philosophy Culture and Political Science, 2018)
Within the framework of the socio-cultural paradigm of the second decade of the 21st century, modern man is most often characterized as a consumer of mass media culture [1, p. 143]. Against the backdrop of the rapid change in the discourse «present-past», it is in a contradictory situation of chronological fluctuations: the present is changing so rapidly that numerous information events were completely irrelevant yesterday. In the logic of postmodern consciousness, the present does not flow from the past and is very indirectly contiguous with the future, and historical events, say, 30-40 years ago, become literally «prehistoric» in the world view of the younger generation. But the danger of forgetting their history is notorious, therefore, it is necessary to rethink the experience of the museification of the past and to find ways to incorporate it into new cultural realities that are adequate to the actual worldview.Key words: culture, modern man, museum, history, young generation.